Estudo e análise de anáforas encapsuladoras : o editorial em foco - Minotto, Lílian Rejane da Costa (2019)
The study aims at the phenomenon of anaphora, especially the encapsulating anaphora and its functioning in the journalistic - editorial text. The research is descriptive, analytical and literature with a qualitative approach. The objective is to carry out a study on textual anaphora, prioritizing the study and analysis of encapsulating anaphora, in editorials, observing its contribution in the construction of the text, as well as its syntactic-semantic functioning. It is used the orientation about the methodological and theoretical principles of the textual linguistics where it is founded mainly at Conte (2003), Koch (1998) and Marcuschi (2003, 2012), Cavalcante (2005), Mondada and Dubois (2003), and Fávero (1991), bearing in mind the importance of teaching Portuguese in school. It is intending to constitute the analysis of corpus starting from identified items in the referential processes present in the text, mainly taking note of the cases of encapsulating anaphora and emphasizing the main strategies used by the author in the elaboration of his editorial. It should be note the analysis of these encapsulating anaphoraes due to the fact that they build sense up to the text, observing its functioning in the text’s internal organization – in this case, the editorial.